PENGARUH BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN MELALUI KOMPETENSI TERHADAP KINERJA PEGAWAI DI KECAMATAN GADINGREJO KOTA PASURUAN - Bramanto Pambudi Sampurno; Sodik; Muchlis Mas’ud (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
The purpose of this study is to analyze and empirically test the influence of organizational culture and leadership style through competence on employee performance. The population in this study were all employees in the Gadingrejo District, Pasuruan City, totaling 55 employees. This study used a census to determine the sample. The data analysis technique used in this study was Partial Least Square-Structural Equation Modeling (PLS-SEM) using smartPLS software version 4. The results showed that organizational culture did not directly affect employee performance. Organizational culture directly affected employee competence. Leadership style did not directly affect employee performance. Leadership style directly affected employee competence. Competence directly affected employee performance. Organizational culture affected employee performance through perfect mediation of competence. Leadership style affected employee performance through perfect mediation of competence